Vertical or asymmetric nystagmus need not imply neurological disease. Issue 2 (1st February 2000) - Shawkat, Fatima S; Kriss, Anthony; Thompson, Dorothy; Russell-Eggitt, Isabelle; Taylor, David; Harris, Christopher
Abstract : AIM: To indicate that congenital idiopathic nystagmus (CIN) and sensory defect nystagmus (SDN) can be vertical or asymmetric in some children. METHODS: Of 276 children presenting with nystagmus for electrophysiological testing, 14 were identified as having CIN or SDN, yet had a nystagmus which was either vertical (n=11) or horizontal asymmetric (n=3). Flash electroretinograms and flash and pattern visual evoked potentials (VEPs) were recorded in all patients. Eye movement assessment, including horizontal optokinetic nystagmus (OKN) testing, was carried out in 11/14 patients. RESULTS: Eight patients (seven with vertical, one with asymmetric horizontal nystagmus) had congenital cone dysfunction. One patient with vertical and another with asymmetric nystagmus had cone-rod dystrophy. One patient with vertical upbeat had congenital stationary night blindness. Two patients (one downbeat, one upbeat nystagmus) had normal electrophysiological, clinical, and brain magnetic resonance imaging findings and were classified as having CIN. One patient with asymmetric nystagmus showed electrophysiological and clinical findings associated with albinism. Horizontal OKN was present in 80% of patients tested, including the three cases with horizontal asymmetric nystagmus. This is atypical in both CIN and SDN, where the OKN is usually absent. CONCLUSIONS: Vertical and asymmetric nystagmus are most commonly associated with serious intracranial pathology and its presence is an indication for neuroimaging studies. However, such nystagmus can occur in children with retinal disease, albinism, and in cases with CIN. These findings stress the importance of non-invasive VEP/ERG testing in all cases of typical and also atypical nystagmus.